Small is beautiful: economics as if people mattered - Schumacher, Ernst Friedrich (Blond & Briggs, 1973)

Organizational Learning: A Theory of Action Perspective - Argyris, Chris; Schon, Donald A. (Addison Wesley, 1978)

Inside Foreign Aid - Tendler, Judith (The Johns Hopkins University Press, 1975)
A classic, important study in the anthropology of development, grounded in the author's own work within USAID, and analysis of the organizational and institutional pressures that constrain and shape development agency employees' cognition and action.
Keywords: IMPORTANT

Adaptive environmental assessment and management - Holling, C. S. (Wiley, 1978)
Keywords: Ecology; Economic development; Environmental impact analysis; Environmental protection